2018
DOI: 10.1371/journal.pone.0190786
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of species-specific ELISA assays to measure IFN-γ and TNF-α in bottlenose dolphins (Tursiops truncatus)

Abstract: Monitoring the immune status of cetaceans is important for a variety of health conditions. Assays to quantify cytokines, especially pro-inflammatory cytokines, could be employed, in addition to currently available diagnostic assays, to screen for alterations in the health status of an animal. Though a number of immunological assays are readily available for humans and mice, specific assays for many veterinary species, including cetaceans such as bottlenose dolphins (Tursiops truncatus), are more limited. Herei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Furthermore, the mRNA expression level of TNF-α was significantly decreased by 1 µg/ml C-AgNP 20 after 24 h of culture. TNF-α is a cytokine specifically useful to measure the inflammatory state of an animal and it is primarily produced by macrophages and both Th1 and Th2 cells in response to both acute and chronic conditions ( Eberle et al, 2018 ). Previous studies have demonstrated that TNF-α is a contributing factor in the inflammatory response against infection of intracellular micropathogens such as Plasmodium spp., T. gondii , Leishmania major , and Trypanosoma spp.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the mRNA expression level of TNF-α was significantly decreased by 1 µg/ml C-AgNP 20 after 24 h of culture. TNF-α is a cytokine specifically useful to measure the inflammatory state of an animal and it is primarily produced by macrophages and both Th1 and Th2 cells in response to both acute and chronic conditions ( Eberle et al, 2018 ). Previous studies have demonstrated that TNF-α is a contributing factor in the inflammatory response against infection of intracellular micropathogens such as Plasmodium spp., T. gondii , Leishmania major , and Trypanosoma spp.…”
Section: Discussionmentioning
confidence: 99%
“…While informative on the distribution of the cell types secreting cytokines in different tissues, this method is limited to the use of tissues from dead animals, or biopsies in live animals, which would be a rather invasive procedure. ELISAs have been developed to measure killer whale-specific IL-6 (57) and dolphin-specific IFNγ and TNFα (58) in serum and tissue culture medium. While sensitive and reproducible under stringent laboratory conditions, ELISAs are relatively time consuming and labor-intensive.…”
Section: Discussionmentioning
confidence: 99%